Education, tradition, and liquid modernity: ambivalences of the Gaúcho Traditionalist Movement: (Práxis Educativa, 2025)
This article investigates the relationship between tradition, memory, and education, considering how, based on Bauman’s reflections on identity, community, and globalization, the Movimento Tradicionalista Gaúcho (MTG) – Gaúcho Traditionalist Movement – operates within liquid modernity to promote a homogeneous regional identity centered on the idealized figure of the white, military, landowning man. To achieve this, it mobilizes a selective and idealized past, offering a sense of belonging and security in the face of contemporary cultural fragmentation, while simultaneously reinforcing exclusions and ambivalences. Drawing on reports published by the State Department of Education of Rio Grande do Sul and by the MTG itself (2003–2022), the study discusses whether it is possible to reconcile the need for identity and belonging with the promotion of inclusion, diversity, and recognition of marginalized groups. It also questions how schools can assert themselves as democratic spaces that mediate between tradition and modernity, balancing cultural identity, plurality, and critical civic education.Keywords: Education. Movimento Tradicionalista Gaúcho. Liquid modernity.